Organopolysiloxane composition with ceramic microspheres

By using Si-H groups and ethylenically unsaturated groups functionalized polysiloxane compositions in lithium-ion batteries, combined with hydrosilylation catalysts and hollow ceramic particles, a compressible, thermally insulated, flame-retardant can be formed. The foamed material solves the problem of insufficient thermal insulation of thermal barrier materials in the prior art and significantly reduces the risk of fire and explosion.

CN119137233APending Publication Date: 2024-12-13DOW SILICONES CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095574.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery thermal barrier materials are insufficient in thermal insulation in high-energy-density battery packs, which is difficult to prevent thermal runaway, and have poor mechanical properties, which increases the risk of fire and explosion.

Method used

Using a composition comprising Si-H group functionalized polysiloxane, ethylenically unsaturated group functionalized polysiloxane, hydrosilation catalyst, flame retardant and hollow ceramic particles , forming a compressible, thermally insulated, and flame-retardant foaming material.

Benefits of technology

The composition material provides effective thermal insulation, flame retardancy and compressibility in lithium-ion batteries, reducing the risk of thermal runaway and fire explosion, and meeting the safety needs of high-energy density battery packs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110615480000071
    Figure BDA0005110615480000071
Patent Text Reader

Abstract

A composition comprising a reactive polysiloxane and a hydroxyl group-containing precursor, a flame retardant, and micron-sized hollow ceramic particles. The composition can be used to prepare insulating, compressible, and flame retardant foam materials that can be used to provide thermal insulation, flame retardancy, and compressibility for applications such as lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The present invention relates to organopolysiloxane compositions containing micron-sized ceramic particles.

[0002] Rechargeable lithium-ion batteries (LiBs) are commonly used in a variety of applications, including electric vehicles (EVs) and grid energy storage systems. Despite the desirable properties of LiBs, including high energy density and stability, safety issues currently limit their usefulness. First, failure of LiB cells can be triggered by manufacturing defects, internal short circuits, overheating, overcharging, or mechanical shock. Second, heat generated from a failed cell can propagate, leading to thermal runaway in adjacent cells. The rapid pressure buildup caused by these thermal events increases the risk of fire and explosion.

[0003] Thermal runaway can be mitigated by placing a thermal barrier between the cells in a LiB module, which provides thermal insulation and flame retardancy. Commonly used thermal barriers such as aerogels, ceramic fibers, and mica sheets offer such properties; however, aerogels and ceramic fibers have poor mechanical elasticity, while mica sheets have poor compressibility. On the other hand, although silicone foam provides sufficient compressibility and is therefore suitable for low and medium energy density batteries, its thermal insulation is insufficient to prevent thermal runaway for very high energy density battery packs. Therefore, in the field of thermal barriers for rechargeable batteries, it is desirable to produce a barrier that provides thermal insulation, flame retardancy, and satisfactory compressibility. Summary of the Invention

[0004] The present invention addresses the needs in the art by providing a composition comprising, based on the weight of the composition, a) 2 to 50 weight percent of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 weight percent of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 weight percent of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b, and component c is in the range of 35 to 95 weight percent, based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 weight percent of a flame retardant; and f) 1 to 35 weight percent of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm.

[0005] The compositions of the present invention can be used to provide foamed materials that serve as compressible, thermally insulating, and flame-retardant separators in lithium-ion batteries. DETAILED DESCRIPTION

[0006] The present invention is a composition comprising, based on the weight of the composition, a) 2 to 50 weight percent of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 weight percent of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 weight percent of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b, and component c is in the range of 35 to 95 weight percent, based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 weight percent of a flame retardant; and f) 1 to 35 weight percent of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm.

[0007] The polysiloxane (a) functionalized with at least two, preferably at least three, Si-H groups has a degree of polymerization ranging from 5 to 1000, or to 500, or to 200. The hydroxyl-containing compound (b) is preferably benzyl alcohol or a C2-C8-alkyl diol. The polysiloxane (c) functionalized with at least one, preferably at least two, ethylenically unsaturated groups has a degree of polymerization ranging from 20, or 100, or 200, or 300 to 2000, or to 1500, or to 1000. The total weight percentage of component a, component b, and component c, based on the weight of the composition, is in the range of 35%, or 50%, to 95%.

[0008] The polysiloxane functionalized with at least one ethylenically unsaturated group is preferably functionalized with two C2-C8 alkenyl groups, more preferably two vinyl or two allyl groups. The polysiloxane functionalized with at least one ethylenically unsaturated group is most preferably a polydimethylsiloxane functionalized with two vinyl groups. The polydimethylsiloxane functionalized with two vinyl groups is advantageously designed to have a viscosity in the range of 10,000 mPa·s to 50,000 mPa·s. This viscosity can be conveniently achieved by combining divinyl-functionalized polydimethylsiloxanes of different degrees of polymerization (i.e., a bimodal distribution of divinyl-functionalized polydimethylsiloxanes).

[0009] The hydrosilylation catalyst is preferably a platinum-based catalyst, such as chloroplatinic acid, and is used in a catalytic amount, typically in the range of 0.5 ppm to 200 ppm Pt based on the weight of the composition.

[0010] The composition also comprises from 1% or 2% or 3% to 30% or to 20% or to 15% by weight of a flame retardant, which is a metal hydroxide, carbonate, hydroxide-carbonate or hydrate that releases CO2 or water or both when heated. Examples of flame retardants include Al(OH)3, Mg(OH)2, Ca(OH)2MgCO3·3H2O (nesquehonite), Mg5(CO3)4(OH)2·4H2O (hydromagnesite), MgCa(CO3)2 (calcium carbonate), AlO(OH) (boehmite), NaHCO3 and hydrated MgSO4 (epsomite).

[0011] The composition also includes 1% by weight or 5% by weight or 10% by weight to 35% by weight or to 30% by weight to 25% by weight of hollow, air-filled or inert gas-filled ceramic particles. As used herein, "ceramic" refers to a crystalline or semi-crystalline inorganic oxide, nitride, carbide, oxynitride or oxycarbide of a metal such as aluminum (e.g., crystalline or semi-crystalline Al2O3), silicon (e.g., crystalline or semi-crystalline SiO2) or calcium (e.g., crystalline or semi-crystalline CaO), or a combination thereof. Crystallinity can be measured by X-ray powder diffraction. As used herein, the term "semi-crystalline" refers to a ceramic material having an amorphous region and a crystalline region. The hollow ceramic particles have a volume average particle size of 25 μm or 50 μm or 70 μm to 300 μm or to 200 μm or to 150 μm, as measured using a dynamic light scattering analyzer such as a Beckman Coulter LS130 particle size analyzer. The resulting product has a particle size of 0.10 g / cm 3 or 0.15g / cm 3 to 0.90g / cm 3 or up to 0.50g / cm 3 Density within the range.

[0012] The composition can be used to prepare polyorganosiloxane foam articles, as essentially described, for example, in US Pat. No. 5,358,975. Advantageously, a polysiloxane functionalized with at least three Si-H groups is contacted with a) an alcohol, diol, polyol or silanol and b) a divinyl-functionalized polydimethylsiloxane in the presence of a platinum-based catalyst to form a crosslinked network of organopolysiloxane having -Si-CH2-CH2-Si- groups and -Si-OR groups, wherein R is a structural unit of an alcohol, diol, polyol or silanol (i.e., a reaction product).

[0013] It may be advantageous to prepare the foam using a two-part process, wherein in a first container, a first part of a divinyl-functionalized polydimethylsiloxane; a first part of a flame retardant; a platinum-based catalyst; one or more hydroxyl-containing compounds; and a first part of hollow ceramic particles are blended to form a Part A composition. In a second container, the remaining part of the divinyl-functionalized polydimethylsiloxane; a polymer resin blend, which is a mixture of a divinyl-functionalized polydimethylsiloxane and a crosslinked organopolysiloxane resin; the remaining part of the flame retardant; a polysiloxane functionalized with at least three Si—H groups; and the remaining part of the hollow ceramic particles are blended to form a Part B composition. Parts A and B are then combined and mixed, and then poured between two release films to form the foam of the present invention.

[0014] Therefore, in another aspect, the present invention is an insulating, compressible and flame retardant foam material comprising, based on the weight of the foam material, 35% to 95% by weight of polyorganosiloxane foam; 1% to 30% by weight of a flame retardant; and 1% to 35% by weight of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm; wherein the foam material has a density of 0.10 g / cm 3 to 0.90g / cm 3 Density within the range.

[0015] In yet another aspect, the present invention is a battery module comprising a housing containing an array of spatially separated battery cells and a polyorganosiloxane foam material that contacts adjacent battery cells. The polyorganosiloxane foam may contact the battery cells by filling the spaces between adjacent battery cells with foam and / or by covering the battery cells with foam. The battery module may also include end plates at the inner edge of the housing that are in direct or indirect contact with the battery cells closest to the edge. The foam material may be inserted into the cavities between adjacent battery cells and in the cavities between the battery cells and the end plates; alternatively, a foam precursor may be applied to the cells and into the cavities and then cured to form the foamed material.

[0016] The foamed materials of the present invention have been found to provide the desirable properties of thermal insulation, flame retardancy, and compressibility in LiB thermal barrier applications.

[0017] In the following examples, ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 Resin M w and M nThe determination was performed by gel permeation chromatography using a gpc column filled with 5-mm diameter divinylbenzene cross-linked polystyrene beads of the pore type Mixed-C (Polymer Laboratory), THF was used as the mobile phase, and detection was performed by a refractive index detector.

[0018] Example 1 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles

[0019] The first component (Part A) was prepared by mixing together using a Flacktek Speed ​​mixer: dimethylvinylsiloxy-terminated polydimethylsiloxane having a viscosity of about 40,000 mPas (Polymer 1, 11.3 pbw); 1) dimethylvinylsiloxy-terminated polydimethylsiloxane having a viscosity of about 1,900 mPas and about 0.22 wt% Vi; and 2) ViMe2SiO 1 / 2 :(CH3)3Si-O 1 / 2 :SiO 4 / 2 The structural unit ratio is 5:40:55, M n is 5000 and M w 21,400 ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 A 64:36 w / w blend of a polyol (polymer-resin blend, 64.9 pbw) and Micral 855 aluminum hydroxide (15.2 pbw) was added to the mixture. The contents were stirred at 2000 rpm for 30 seconds, after which a complex of Pt(0) and divinyltetramethyldisiloxane (0.93 pbw, 0.62 wt% Pt), 1,4-butanediol (2.6 pbw), and benzyl alcohol (3.3 pbw) were added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds. Finally, Elminas Spheres HCMS-W150 hollow ceramic particles (volume average particle size of 100 μm; 20 pbw) were added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds.

[0020] The contents were stirred at 2000 rpm for 30 seconds, after which a complex of chloroplatinic acid and divinyltetramethyldisiloxane (0.93 pbw, 0.62 wt% Pt), 1,4-butanediol (2.6 pbw), and benzyl alcohol (3.3 pbw) were added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds. Finally, Elminas Spheres HCMS-W150 hollow ceramic particles (volume average particle size of 100 μm; 20 pbw) were added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds.

[0021] A second composition (Part B) was similarly prepared by mixing together Polymer 1 (8.9 pbw), a polymer resin blend (51 pbw), and Hymod M855 aluminum hydroxide (26.4 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a linear organohydrogenpolysiloxane having a viscosity of 30 mPa·s and a SiH content of 1.6 wt% (6.7 pbw) and a polydimethylorganohydrogensiloxane having a viscosity of 5 mPa·s and a SiH content of 0.7 wt% (5.1 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds. Elminas Spheres HCMS-W150 hollow ceramic particles (20 pbw) were then added to the mixture and the contents were stirred at 2000 rpm for 30 seconds.

[0022] Equal amounts of Part A and Part B were then mixed and the mixture was poured between two release films (matte mylar film). A roller was used to control the initial (pre-foaming) thickness to 0.045 inches. The sample was cured at 70°C for 5 minutes and then at 100°C for 15 minutes to produce a foam sheet for further testing. (Density = 0.31 g / cm 3 )

[0023] Example 2 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles

[0024] In addition to using Elminas Spheres HCMS THERMO-W75 hollow ceramic particles (volume average particle size 80 μm, 20 pbw) (density = 0.31 g / cm 3 ), the method for preparing the foamed article of Example 1 was performed in substantially the same manner.

[0025] Example 3 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles

[0026] In addition to using Elminas Spheres HCMS-W300 hollow ceramic particles (volume average particle size of 180 μm, 20 pbw) (density = 0.34 g / cm 3 ), the method for preparing the foamed article of Example 1 was performed in substantially the same manner.

[0027] Thermal insulation and flammability

[0028] The thermal insulation and flammability of the foams prepared as described in the examples were tested using a hot plate set on a hydraulic press. The hot plate was set at 600°C with an insulator on top of the surface. Four thermocouples (K type) were fixed to an aluminum heat sink (4" x 4" x 0.47") using Kapton tape. The sample (4" x 4") was then placed and fixed to the heat sink using Kapton tape. Another thermocouple (K type) was attached to the sample surface using Kapton tape. The insulator was removed from the hot surface and the sample attached to the heat sink was quickly placed onto the hot surface so that the sample surface faced the hot plate surface and the Al heat sink faced the opposite side. The pressure was quickly increased to 355kPa. A data logger was used to record the interface temperature between the hot plate surface and the sample surface and the interface temperature between the sample surface and the heat sink. Once the time reached 300 seconds, the pressure was released and the test was terminated. A sample surface temperature of <300°C was considered acceptable. No observable flames throughout the test were considered acceptable flame retardancy.

[0029] hardness

[0030] Measure hardness using a Shore 00 durometer. Place the test specimen on a hard, flat surface. Then, press the indenter of the Shore 00 durometer onto the specimen, ensuring it is parallel to the surface. Read the hardness while it remains in firm contact with the specimen. A hardness of <80 is considered acceptable.

[0031] Compression force

[0032] Compression force is measured using a TA.HDplus Texture Analyzer equipped with a 100 kg load cell, a 40 mm diameter aluminum probe, and a flat, heavy-duty aluminum baseplate. A silicone foam sample is cut into a circular shape using a 1" diameter die cut and placed between the baseplate and the probe. The probe is initially set at the same height as the sample thickness and lowered at a rate of 1 mm / s until the maximum pressure is reached. The sample thickness and pressure are recorded as a compression force curve. The pressure is recorded at 30% of the initial sample thickness. A compression force of <500 kPa is considered acceptable.

[0033] Foam density

[0034] The foam density was calculated based on the average thickness and weight of two foam samples having a diameter of 1 inch.

[0035] The properties of the ceramic-filled organopolysiloxane articles were compared to a commercial organopolysiloxane article (COHRlastic silicone foam, available from Stockwell Elastomerics) that was similar in construction to the example foams except that it did not contain the hollow ceramic particles.

[0036] Table 1 is a summary of the performance characteristics of the foams of Examples 1 to 3 and commercial comparative foams. Density is in g / cm 3 measurements; hardness is measured in Shore 00 units; compression force (force) is measured in kPa at 30% compression; temperature at 600°C (T after 300 seconds) refers to the sample surface temperature after 300 seconds; and flammability refers to the observability of flames during the thermal insulation test.

[0037] Table 1 - Properties of organopolysiloxane products

[0038]

[0039] Table 1 shows that the foam of the present invention passed all tests, while the commercial example failed the thermal insulation test. It has been surprisingly found that the hollow ceramic particles reduce the surface temperature at 300 seconds without adversely affecting other key properties of the foam. It has also been found that hollow ceramic particle sizes in the range of 50 μm to 150 μm are particularly effective in reducing surface temperature.

Claims

1. A composition comprising, based on the weight of the composition: a) 2 to 50% by weight of a polysiloxane functionalized with at least two Si—H groups and having a degree of polymerization in the range from 5 to 1000; b) 1 to 50% by weight of water, alcohols, diols, polyols or compounds containing one or more silanol groups; c) 10% to 90% by weight of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of component a, component b and component c is in the range of 35% to 95% by weight, based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 wt % of a flame retardant; and f) 1 to 35 wt. % of hollow ceramic particles having a volume average particle size in the range of 25 to 300 μm.

2. The composition of claim 1, wherein the polysiloxane functionalized with at least two Si-H groups is functionalized with at least three Si-H groups; the total concentration of component a, component b and component c is in the range of 50% to 80% based on the weight of the composition; and the concentration of the flame retardant is in the range of 2% to 20% by weight based on the weight of the composition.

3. The composition according to claim 2, wherein the polysiloxane functionalized with at least one ethylenically unsaturated group is a divinyl-functionalized polydimethylsiloxane having a degree of polymerization ranging from 100 to 1000.

4. The composition according to claim 3, wherein the flame retardant is one or more flame retardants selected from the group consisting of Al(OH)3, Mg(OH)2, MgCO3·3H2O, Mg5(CO3)4(OH)2·4H2O, MgCa(CO3)2, AlO(OH), NaHCO3 and hydrated MgSO4.

5. The composition according to any one of claims 1 to 4, wherein the hollow ceramic particles have a volume average particle size in the range of 25 μm to 200 μm as measured by dynamic light scattering.

6. The composition according to any one of claims 1 to 4, wherein the hollow ceramic particles have a volume average particle size in the range of 50 μm to 150 μm as measured by dynamic light scattering.

7. The composition according to claim 5 or 6, wherein the hollow ceramic particles are crystalline or semi-crystalline Al2O3 particles, crystalline or semi-crystalline SiO2 particles, or crystalline or semi-crystalline CaO particles.

8. The composition of claim 3, wherein the divinyl functionalized polydimethylsiloxane is a bimodal distribution of divinyl functionalized polydimethylsiloxanes having a combined viscosity in the range of 10,000 mPa·s to 50,000 mPa·s.